IMPLEMENTASI TARIF RETRIBUSI PARKIR BERDASARKAN PERATURAN DAERAH KOTA TANGERANG NOMOR 3 TAHUN 2014 TENTANG RETRIBUSI JASA USAHA - Muhammad Naufal Alfaraz; Rasji Rasji (Fakultas Hukum Universitas Tarumanagara, 2022)
Parking retribution are one source of Regional Original Income which has a high enoughpotential for financing regional expenditures in carrying out government and development tasks.Therefore, it is very necessary to have a legal certainty for the application of parking retributionrates regulated by the Regional Government based on applicable laws and regulations. How is theimplementation of the parking retribution rate based on the Tangerang City Regional RegulationNumber 3 of 2014 about Business Service Retribution? What are the obstacles to deal with inimplementing the parking rates? The author examines this problem by using empirical legalresearch methods. Research data shows that parking management in Tangerang City was managedby PT TNG as a BUMD since March 2018 based on the Tangerang Mayor Regulation, withparking managed by PT TNG it makes regional original income from parking fees is not optimal, itis happens because of parking who managed by BUMD is excluded from the object of parkingretribution. From the data on the realization of Tangerang City's original revenue in 2018 and2019, it also shows an insignificant profits. Of course this is due to the obstacles faced by PT TNG,there are the parking rates regulated by the Regional Regulation are too cheap considering thecurrent economic growth, then in its operations PT TNG is obliged to rent a land to the TangerangCity Government and also pay a tax of 20% (twenty percent) every month to be deposited into theregional treasury.